How We Think: How it Affects Sustainable Thinking - Kras, Eva (Problemy Ekorozwoju, 2015)
Our present model related to Sustainable Development has followed our current day way of thinking, that is, it depends heavily on the use of rational and logical thinking. With this dominant system of thinking we have been having only limited success in the whole world of Sustainable Development. Following the new research by Iain McGilchrist, related to Right and Left Hemisphere brain thinking processes, and its long history we are now being able to see more clearly the actual work of each hemisphere. In the conventional process to date most right hemisphere brain thinking in organizations has somehow become excluded over many generations, and in society as a whole only left brain logical, rational thinking has been accepted as valid. Now we have new research that reveals some incredible and different abilities that indicate clearly the Genuine Value of our right brain in our overall thinking about Life and Work in our society in general. This new research turns the table as such, allowing the right hemisphere of our brain its true and indispensible role for ALL sustainable development work. This short paper develops these revelations and their benefits for humanity and our organizations in all we attempt to do every day everywhere. As a result, we will then truly begin to accept that the right hemisphere of our brain is our Master and the left hemisphere is our Emissary. This new research forms a genuine and careful place for the Right hemisphere in all that we plan in life and work every day as well as the importance of the left hemisphere as its Emissary, (not the Master as is presently the case), as well as a new viable Balance between all Right and Left brain thinking in all dimensions of business, community development and everyday life.